Skin biological responses to urban pollution in an ex vivo model. (15th September 2021) - Patatian, A.; Delestre-Delacour, C.; Percoco, G.; Ramdani, Y.; Di Giovanni, M.; Peno-Mazzarino, L.; Bader, Th.; Bénard, M.; Driouich, A.; Lati, E.; Benech, P.; Follet-Gueye, M.L.
Highlights: Exposure of human skin explants to urban pollutant mixture via the Pollubox® chamber. Skin alterations were recorded down to the stratum basale . Pollutant exposure induces relevant xenobiotic and anti-oxidant responses. The model developed herein is able to test anti-pollutant cosmetic products. Abstract: The skin epidermis is continuously exposed to external aggressions, including environmental pollution. The cosmetic industry must be able to offer dedicated products to fight the effects of pollutants on the skin. We set up an experimental model that exposed skin explants maintained in culture to a pollutant mixture. This mixture P representing urban pollution was designed on the basis of the French organization 'Air Parif' database. A chamber, called Pollubox®, was built to allow a controlled nebulization of P on the cultured human skin explants. We investigated ultrastructural morphology by transmission electron microscopy of high pressure frozen skin explants. A global transcriptomic analysis indicated that the pollutant mixture was able to induce relevant xenobiotic and antioxidant responses. Modulated detoxifying genes were further investigated by laser micro-dissection coupled to qPCR, and immunochemistry. Both approaches showed that P exposure correlated with overexpression of detoxifying genes and provoked skin physiological alterations down to the stratum basale . The model developed herein might be an efficient tool to study the effects of pollutants on skin as well as a powerful testing method to evaluate the efficacy of cosmetic products against pollution.